Migração, trabalho e representação: um estudo de caso sobre a Coalition of Immokalee Workers, Flórida - Pera, Géssica Trevisan [UNESP] (2015)
This research analyzes the emergence and development of new forms of organization and representation of migrants farmworkers in the United States. Extremely necessary for the country's economy, these workers were excluded throughout history of social benefits and prevented from organizing themselves legally. However, although they occupy the lowest rung of the production chain, where American citizens refuse to work, subject to a precarious reality of social invisibility, these workers are not characterized by passivity. It is in this context that we focus our eyes in order to understand how a group of immigrants in the southern of Florida, where is located the agricultural region of Immokalee has developed a resistance movement to this condition. Characterized as an important center of agricultural production in the country, annually this region demand thousands of workers to work in citrus and vegetable crops. Tired of frequent irregularities in the fields and, from common interest for better conditions of life and work, a group of immigrant workers founded in 1993, the Coalition of Immokalee Workers (CIW), an organization of community-based non-profit that comes looking over these twenty years represent the tomato pickers that are not covered by social benefits in the country. Nationally recognized, the organization has the support of various segments of society and that principlet: Consciousness + Commitment = Change